The contact mechanics and occurrence of edge loading in modular metal-on-polyethylene total hip replacement during daily activities. Issue 6 (June 2016) - Hua, Xijin; Li, Junyan; Jin, Zhongmin; Fisher, John
Highlights: The contribution of patient daily activities to edge loading was investigated. Edge loading was predicted during normal walking, ascending and descending stairs activities. No edge loading was observed during standing up, sitting down and knee bending activities. Edge loading caused elevated contact pressure and equivalent plastic strain of liner. Abstract: The occurrence of edge loading in hip joint replacement has been associated with many factors such as prosthetic design, component malposition and activities of daily living. The present study aimed to quantify the occurrence of edge loading/contact at the articulating surface and to evaluate the effect of cup angles and edge loading on the contact mechanics of a modular metal-on-polyethylene (MoP) total hip replacement (THR) during different daily activities. A three-dimensional finite element model was developed based on a modular MoP bearing system. Different cup inclination and anteversion angles were modelled and six daily activities were considered. The results showed that edge loading was predicted during normal walking, ascending and descending stairs activities under steep cup inclination conditions (≥55°) while no edge loading was observed during standing up, sitting down and knee bending activities. The duration of edge loading increased with increased cup inclination angles and was affected by the cup anteversion angles. Edge loading caused elevated contact pressure at the articulating surface and substantially increased equivalent plastic strain of the polyethylene liner. The present study suggested that correct positioning the component to avoid edge loading that may occur during daily activities is important for MoP THR in clinical practice.